EFFICACY OF SEED DRESSING INSECTICIDES AT DIFFERENT DOSES FOR THE CONTROL OF SORGHUM SHOOT FLY ATHERIGONA SOCCATA (ROND.) (DIPTERA: MUSCIDAE) - KHALIQ, A; MASOOD, SA; RAUF, HA; FAHEEM, U; MAHMOOD, K; BASIT, A; NADEEM, M; JABBAR, A; KHAN, AA; MUHAMMAD, T (Biological and Clinical Sciences Research Journal, 2022)
Shoot fly, Atherigona soccata (Rondani); an invasive pest of sorghum/jowar. Selection of proper pesticide with suitable doze is the key to economical and effective control of shoot fly. Field experiments were conducted for two consecutive years 2014-2015 during kharif season in Fodder Research Institute, Sargodha-Pakistan to find out the impact of three seed dressing insecticides at different doses (Confidor @ 2.5g, 5g, 7.5g& 10g, Actara 2.5g, 5g& 7.5g and Hombre 2ml, 4ml& 6ml) for the control of sorghum/jowar shoot-fly. It was observed that all treated plots showed significantly lower dead hearts percentage caused as compared to control. Amongst chemicals the treatment with Actara (thiamethoxam) @ 7.5g and 5g/kg seed recorded significantly lowest dead hearts (11.5, 11.9%) and gave maximum yield (1.79,1.73 t/h). Therefore, to avoid and reduce toxic effects of direct spray on sorghum against shoot fly and to maximize the yield it is recommended to use thiamethoxam @ 5 g/kg as a seed dressing insecticides for both fodder and seed crop of sorghum.